Berkeley and Sensible Things - Rizky Yazid (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This paper aims to re-reading Berkeley and reposition his philosophy of knowledge between the claims of adherents of idealism or immaterialism that so far have been labeled by interpreters. In other words, the label as an adherent of idealism or immaterialism is not a position stated by Berkeley himself, but the result of interpreters reading the consequences of Berkeley's philosophy of knowledge. Those who called Berkeley an idealist included: Georges Dickers, Robert G. Meyers and Robert J. Fogelin. His assumption, citing Dickers, branded Berkeley as an idealist because of Berkeley's view that there are only ideas and thoughts rather than physical objects. Meanwhile, those who label Berkeley as adherents of immaterialism include: I.C. Tipton, David Berman. His assumption cites Berman that Berkeley's labeling of immaterialism is hypothetical and a consequence of his philosophical views. This study uses a descriptive method, where relevant texts are collected first as research objects, which the writer then describes as variables. The status variable itself has no influence or relationship or correlation with other variables. The findings of this study are that both interpreting Berkeley as immaterialist and idealist are related to Berkeley's rejection of religious skepticism. In addition, labeling as an immaterialist or idealist comes from the interpretation of Berkeley's schoolar on the consequences of Berkeley's rejection of physical objects that are independent of the subject's mind.